(2+2y^2)dx+3xy^2dy=0
Answer:
"\\dfrac {3}{2y}ln|1+y^2| + ln|\\dfrac {A}{x^2}| - 3y = 0"
Solution
"(2+2y^2)dx + 3xy^2dy = 0"
Separating terms gives:
"3xy^2dy = -2(1+y^2)dx"
dividing both sides by "x(1+y^2)" gives:
"\\dfrac {3xy^2}{x(1+y^2)}dy = \\dfrac {-2(1+y^2)}{x(1+y^2)}dx"
"=> \\dfrac {3y^2}{1+y^2}dy = \\dfrac {-2}{x}dx"
Reducing "\\dfrac {y^2}{1+y^2}" will give:
"\\dfrac {y^2}{1+y^2} = 1 - \\dfrac{1}{1+y^2}"
"=> 3(1-\\dfrac {1}{1+y^2})dy = \\dfrac{-2}{x}dx"
Integrating both sides gives:
"\\intop3(1-\\dfrac {1}{1+y^2})dy = \\intop\\dfrac{-2}{x}dx"
"=> 3\\intop(1-\\dfrac {1}{1+y^2})dy = -2\\intop\\dfrac{1}{x}dx"
"=> 3(y-\\dfrac{1}{2y}ln|1+y^2|=-2ln|x|+ln(A)"
"=> 3y - \\dfrac{3}{2y}ln|1+y^2| = ln|x^{-2}| + ln(A)"
"=> 3y = \\dfrac {3}{2y}ln|1+y^2| + ln|\\dfrac {A}{x^2}|"
"\\dfrac {3}{2y}ln|1+y^2| + ln|\\dfrac {A}{x^2}| - 3y = 0"
Comments
Leave a comment